Strategies to promote tendon-bone healing after anterior cruciate ligament reconstruction: Present and future - Tian, Bin; Zhang, Ming; Kang, Xin (Frontiers in Bioengineering and Biotechnology, 2023)
At present, anterior cruciate ligament (ACL) reconstruction still has a high failure rate. Tendon graft and bone tunnel surface angiogenesis and bony ingrowth are the main physiological processes of tendon-bone healing, and also the main reasons for the postoperative efficacy of ACL reconstruction. Poor tendon-bone healing has been also identified as one of the main causes of unsatisfactory treatment outcomes. The physiological process of tendon-bone healing is complicated because the tendon-bone junction requires the organic fusion of the tendon graft with the bone tissue. The failure of the operation is often caused by tendon dislocation or scar healing. Therefore, it is important to study the possible risk factors for tendon-bone healing and strategies to promote it. This review comprehensively analyzed the risk factors contributing to tendon-bone healing failure after ACL reconstruction. Additionally, we discuss the current strategies used to promote tendon-bone healing following ACL reconstruction.